2019
DOI: 10.4103/ijem.ijem_24_19
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and its association with glycemic control in type 2 diabetes mellitus patients

Abstract: Introduction: Type 2 diabetes mellitus is one of the major causes of increasing morbidity worldwide. Effective screening is carried out routinely for diabetic retinopathy, neuropathy, and nephropathy. Of late, studies have reported that cognitive decline can occur in people with diabetes, which could go undetected for a long period, and hence routine screening could be warranted. Methodology: Our objective was to study the prevalence of previously unknown mild cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…No difference was found in the blood biochemical assessment between the two groups in this study (Table 8). Previous studies reported that MCI participants had higher fasting blood glucose, post-meal blood glucose, and HbA1c compared to healthy participants and had a higher risk of neuropathy-induced cognitive impairment [57,58]. In this study, the MCI group had higher FPG, which was defined as impaired glucose intolerance (≥100 and <126 mg/dL).…”
Section: Body Composition and Blood Biochemical Parametersmentioning
confidence: 68%
“…No difference was found in the blood biochemical assessment between the two groups in this study (Table 8). Previous studies reported that MCI participants had higher fasting blood glucose, post-meal blood glucose, and HbA1c compared to healthy participants and had a higher risk of neuropathy-induced cognitive impairment [57,58]. In this study, the MCI group had higher FPG, which was defined as impaired glucose intolerance (≥100 and <126 mg/dL).…”
Section: Body Composition and Blood Biochemical Parametersmentioning
confidence: 68%
“…This study set the statistical power at 80 % and α value at 5 %. The minimum sample size was 133 based on the correlation coefficient formula and the value of r in the previous studies [ [17] , [18] , [19] ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies reporting a higher incidence of mild MCI in patients with T2DM. Specifically, sociodemographic factors were associated with cognitive impairment in 50% of the diabetic study population, and another study demonstrated statistically significant MCI in T2DM patients with higher levels of HbA1C, FBS, and PPBS levels [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%